A Christian Value? Faculty Diversity at Southern Evangelical Campuses. Issue 3 (26th May 2016) - Smith, Marquita; Mamiseishvili, Ketevan
ABSTRACT: This case study research project examined efforts at three member institutions of the Council for Christian Colleges & Universities (CCCU), all located in the southern United States, to increase faculty diversity. The study also explored how these efforts related to institutional mission and what aspects within the history of evangelicalism were perceived to promote or hinder the hiring of diverse faculty at these institutions. The study participants consisted of eleven faculty members, seven administrators, and two students from the three case study universities, and one administrator from the main office of the CCCU. Data were analyzed from a combination of personal interviews, observations, field notes, documents, and textual analysis, resulting in the identification of themes related to faculty diversity. Although these institutions had made great strides in diversity efforts, the study findings revealed that more intentional and systematic processes need to be established in order to increase faculty diversity. Given that faculty diversity efforts can be enhanced by implementing better recruitment and retention strategies, the discussion section highlights initiatives that have been effective at these universities, including the active pursuit of faculty of color and the purposeful management of mentorship programs.